Economy operations at your service plus. (Orlando, FL Educational Institute of the American Hotel & Motel Association, 1999)
Discusses the full range of front office skills in thecontext of economy lodging. Combines the training in front office skills, operations and superior guest relations that always place the guest first. Covers hotel front desk service procedures for greeting the guest, registration, room assignment, discussing payment, check-in options.
VHS
Keywords: Hotel front desk personnel -- Training of